A Matter of Life or Death: A Survey Experiment on the Perceived Legitimacy of Political Decision-Making on Euthanasia. Issue 3 (10th April 2019) - Christensen, Henrik Serup; Himmelroos, Staffan; Setälä, Maija
Abstract: Most representative democracies seem to experience dwindling levels of legitimacy in the eyes of citizens. Nevertheless, it remains unclear what people want from parliamentary decision-making. In this study, we test the impact of outcome favourability, actor involvement and justifications on the perceived legitimacy of a parliamentary decision-making process on euthanasia in Finland. We do so with the help of a survey experiment (n = 1243), where respondents were exposed to a vignette where the treatments varied randomly. The results suggest that outcome favourability is of primary importance, but the involvement of experts and citizens also boost legitimacy in the eyes of citizens. Justifications, or presenting arguments for the decisions, does not enhance legitimacy and may even cause a backfire mechanism where the difference between getting and not getting the preferred outcome is amplified.